Genotype determination of megalocytivirus from Indonesian Marine Fishes - MURWANTOKO MURWANTOKO; DINI WAHYU KARTIKA SARI; CHRISTINA RETNO HANDAYANI; RICHARD J. WHITTINGTON (Society for Indonesian Biodiversity, 2018)
Murwantoko, Sari DWK, Handayani CR, Whittington RJ. 2018. Genotype determination of megalocytivirus from Indonesian Marine Fishes. Biodiversitas 19: 1730-1736. Megalocytivirus is the newest genus within the family of Iridoviridae which can be divided into groups represented by red sea bream iridovirus (RSIV), infectious spleen and kidney necrosis virus (ISKNV) and turbot reddish body iridovirus (TRBIV), threespine stickleback iridovirus (TSIV). This virus caused serious systemic disease in cultured marine fishes for consumption and ornamental freshwater fishes with significant mortality. The objective of this study was to determine the genotype of megalocytivirus which infected marine fishes from Lampung, Karimun Jawa, Situbondo and Batam based on major capsid protein (MCP), ATPase, DNA polymerase, CY15 and IRB6. The liver, spleen and kidney tissues of humpback grouper (Cromileptes altivelis), tiger grouper (Epinephelus fuscoguttatus), baramundi (Lates calcarifer) were fixed in 10% phosphate-buffered formalin for histological and fixed in 70% ethanol for molecular analysis. Molecular analysis was performed by amplification of MCP, ATPase, DNA polymerase, CY15 and IRB6 genes and followed by sequencing. Genotype was determined by alignment of the sequences with various genotypes of megalocytivirus from Genbank. Histological examination showed that hypertrophy, inclusion body forming bearing cells were found in liver, spleen and kidney tissues. Polymerase chain reaction with MCP primer produced specific DNA bands. Those results confirmed the infection of megalocytivirus on marine cultured fish samples. The analysis from 10 isolates on five genes revealed that two genotypes of megalocytivirus as infectious spleen and kidney necrosis virus (ISKNV) and red sea bream iridovirus (RSIV) genotypes were existed in Indonesia. The ISKNV genotype was confirmed in fish samples from Lampung, Jepara, Bali; while RSIV genotype was found in fishes from Batam, and Situbondo. Interestingly, both ISKNV and RSIV genotypes were confirmed in fish samples from Karimun Jawa. This paper is the first report on the present of ISKNV and RSIV genotypes in Indonesia based on MCP, ATPase, DNA polymerase, CY15 and IRB6 genes.